A knight in politics : a biography of Sir Frederick Borden - Miller, Carman, 1940- (McGill-Queen's University Press, 2010)
Sir Frederick Borden (1847-1917), physician and entrepreneur, was Canada's longest-serving minister of defence. His untidy private life, however, often captured more attention than his public service. This book explores the history of the controversial public figure who led Canada's armed forces through the South African War.